High Performance In Cloud Computing - Rafique, Noorjahan Mohammed; Sajjan, RS (International Journal of Computer Sciences and Engineering, 2025)
HPC applications nowadays are gaining huge attention in cloud computing arena. Majority of the HPC applications are used for scientific applications or purposes. They require huge CPU usage and tremendous data storage capabilities. Previously HPC applications required large set of interconnected computers in a network like clusters or supercomputers. These clusters are infeasible both financially and technically. But nowadays due to the advent of cloud computing scientific fraternity is able to reap the benefits of cloud computing due to the low cost and maintenance associated with HPC applications. Cloud computing also provides the benefits of Infrastructure as a Service (IaaS) and Platform as a Service(PaaS) both beneficial to the scientific community. Also Quality of Service(QoS) is an added advantage. This paper focuses on the present state of HPC applications as well as previous research done in this field.